Pengaruh Penerapan Aktivitas Mandiri : Upaya Perawatan Orang Dalam Gangguan Jiwa (ODGJ) Defisit Perawatan Diri Didesa Talang Empat Bengkulu Tengah 2023 - Evriani, Chevty; Saputri, Resi Ade; Reginanda R, Bunga; Putri, Tika Azizah; Alfiansyah, Frans; Direja, Ade Herman Surya (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Self-care deficit is a condition in which a person experiences a weakness in the ability to complete self-care activities independently such as bathing, grooming, eating and urinating. Signs and symptoms of self-care deficit include being lazy about bathing, not wanting to comb your hair, not wanting to brush your teeth, not wanting to cut your nails, not wanting to decorate/dress up, not being able to use cleaning tools/bathing equipment. The aim of this research is to help patients increase the degree to which clients maintain cleanliness, improve self-care to prevent disease and increase the client/patient's sense of comfort. The implementation method for this activity is the implementation of SPTK on self-care deficit ODGJ which was carried out in Talang village, four of Bengulu district, in the middle of Bengkulu city. Meanwhile, this research was carried out on 16-18 October 2023. After carrying out this activity, you can find out how to carry out self-care by straightening the client's clothes, cutting nails and washing the face so that it can be done independently. Patients are trained to carry out self-care as taught or not to carry out self-care deficits